Modified atmosphere storage (mas) buah pisang - Wina Libyawati; I Gede Eka Lesmana; A. Raynold; Hafidan Agustian; L. Mahardhika (Universitas Mataram, 2017)
Healthy life style based on natural food consumption, has been implemented by the society to increase health quality. Minimally processed technology is used to slow down food decay time in the storage room. Minimally processed techology is consist of Controlled Atmosphere Storage (CAS), Modified Atmosphere Storage (MAS), Freeze Driying, and blansir. MAS is food storage technology by conditioning the air composition (especially oxygen level). Banana is an object of MAS implementation, due to its all session fruit and shorter life time. Previous MAS studies used long bean as the object and managed to improve the life time until 15 days.The purpose of this study is to implement MAS to lengthen banana life time. MAS design use Ulrich Eppinger method. Simulation of Turbulance Kinetic Energy (TKE) in the sparger and MAS installation use ANSYS 16.2. The experimental to test sparger and installation is conducted for 6 hours for the sparger and 24 hours for the installation. Afterward the correlation between parameter is calculated by using least square method. The outcome of this research is MAS for banana in order to be used by SME with capacity of 4.77 m3, mixture time is 24 hours, TKE number in the sparger is 582.6448 J/kg, TKE number in the installation is 715.6 J/kg, oxygen level in the sparger is 5.7%, oxygen level in MAS installation is 8.5%, glucose of banana located in the storage room is 9.5%, and banana life time able to achiave 14 days.